Communication Strategy of New Media Art to City Image under Smart City Information Technology - Xie, Chen; Chen, Yunfeng; Sun, Qian (Mathematical problems in engineering, 2022)
City image, as a public image, is the public’s overall evaluation and cognition of the city, including concept image, behavior image, and visual image. The new media art is an interdisciplinary research field integrating art, informatics, and communication. It emerged and developed in the new media era and effectively reached the agreement of scientific and technological means and artistic expression. This paper expounds the concept and connotation of smart city informatization and then constructs a measurement model of smart city informatization construction level based on GCD_BPNN. The degree of satisfaction of city image communication in H city was measured, the index evaluation system of system satisfaction in H city was constructed, and the comprehensive satisfaction scale of cultural system in H city was formed. The research shows that the communication of city image in the future should focus on the virtual space and construct the cultural identity and psychological identity of city image from the user’s point of view.